Analisis Hubungan Bauran Pemasaran Terhadap Keputusan Konsumen dalam Pembelian Produk Mie Musbar di Kecamatan Sukajadi Kota Pekanbaru - Sefira, Tri; Yusmini, Yusmini; Eliza, Eliza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Competition in the wet noodle business in Pekanbaru City has had a major impact on UMKM Musbar Noodle which have experienced a decline in production due to declining consumer demand. This research aims to determine consumer characteristics in purchasing Musbar Noodle products, to determine consumer assessments of the 7P marketing mix for purchasing Musbar Noodle products in Sukajadi District, Pekanbaru City. This research was conducted in Mie Musbar, Sukajadi District, Pekanbaru City. The sampling method uses survey and interview methods. Sampling used a non-probability sampling method, namely purposive sampling with a sample size of 60 respondents. Data analysis used in this research used quantitative descriptive analysis and Spearman rank correlation analysis. The first and second objectives were analyzed using quantitative descriptive analysis and the third objective used Spearman rank correlation analysis. Consumer assessment of the 7P marketing mix as a whole is considered good by consumers. The relationship between the 7P marketing mix and consumer decisions has a very strong, strong and quite strong and significant relationship.